Error Estimates of Finite Element Methods for Stochastic Fractional Differential Equations (Journal of Computational Mathematics, 2018)
This paper studies the Galerkin finite element approximations of a class of stochastic fractional differential equations. The discretization in space is done by a standard continuous finite element method and almost optimal order error estimates are obtained. The discretization in time is achieved via the piecewise constant, discontinuous Galerkin method and a Laplace transform convolution quadrature. We give strong convergence error estimates for both semi-discrete and fully discrete schemes. The proof is based on the error estimates for the corresponding deterministic problem. Finally, the numerical example is carried out to verify the theoretical results.